2006 International Conference on Parallel Processing (ICPP'06) 2006
DOI: 10.1109/icpp.2006.74
|View full text |Cite
|
Sign up to set email alerts
|

Vector Lane Threading

Abstract: Multi-lane vector processors achieve excellent computational throughput for programs with high data-level parallelism (DLP). However, application phases without significant DLP are unable to fully utilize the datapaths in the vector lanes. In this paper, we propose vector lane threading (VLT), an architectural enhancement that allows idle vector lanes to run short-vector or scalar threads. VLTenhanced vector hardware can exploit both data-level and thread-level parallelism to achieve higher performance. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Espasa and Valero 15 showed that ILP and DLP can be merged in a single simultaneous vector multithreaded architecture to execute regular vectorizable code at a performance level that cannot be achieved using either paradigm on its own. Rivoire et al 16 proposed vector lane threading (VLT) that allows idle vector lanes to run short-vector or scalar threads by partitioning the vector lanes across several threads. Krashinsky 17 proposed a vector-thread (VT) architecture, which uni¯es the vector and multithreaded compute models.…”
Section: Related Workmentioning
confidence: 99%
“…Espasa and Valero 15 showed that ILP and DLP can be merged in a single simultaneous vector multithreaded architecture to execute regular vectorizable code at a performance level that cannot be achieved using either paradigm on its own. Rivoire et al 16 proposed vector lane threading (VLT) that allows idle vector lanes to run short-vector or scalar threads by partitioning the vector lanes across several threads. Krashinsky 17 proposed a vector-thread (VT) architecture, which uni¯es the vector and multithreaded compute models.…”
Section: Related Workmentioning
confidence: 99%
“…Our technique is complementary to Vector Lane Threading (VLT) [24] and the Vector-Thread (VT) Architecture [14]. VLT assigns groups of lanes to different user-level threads; lanes belonging to the same user-level thread execute in SIMD, but they do not need to execute in lockstep with lanes in other groups.…”
Section: Related Workmentioning
confidence: 99%
“…Vector Architectures: Vector architectures [32,10,21,31,2,4] have a distinct programming model, execution model, and workload characteristics compared to GPGPU architectures. However, the intra-warp compaction techniques proposed in this paper are similar to density time optimizations for addressing vector control flow divergence.…”
Section: Related Workmentioning
confidence: 99%